A qualitative exploration of barriers and facilitators to fruit and vegetable consumption among Uruguayan adults using the social ecological model - Machín, Leandro; Girona, Alejandra; Salgado, Silvina; Marrero, Cecilia; Giménez, Ana; Curutchet, María Rosa; Ares, Gastón (Frontiers in Public Health, 2025)
IntroductionFruit and vegetable consumption remains below public health recommendations worldwide. This study aimed to explore perceived barriers and facilitators to fruit and vegetable consumption among adults living in urban areas outside the capital city of Uruguay, and to identify strategies to promote intake.MethodsThe study relied on a generic qualitative study using focus group discussions. Five focus groups were conducted between October 2024 and April 2025 in three cities in Uruguay (Atlántida, Paysandú, and Tacuarembó), involving 50 adults aged 18 to 77 years, diverse in sociodemographic backgrounds. Transcripts were analyzed using qualitative content analysis, combining inductive identification of emergent categories from the interview transcripts with deductive coding based on the levels of influence of the Social Ecological Model.ResultsAlthough participants widely recognized the health benefits of fruit and vegetable consumption, most reported inadequate intake and described challenges in sustaining regular consumption. Barriers emerged across multiple levels of influence, including individual (e.g., taste preferences, lack of motivation, limited cooking skills), interpersonal (e.g., household composition and income), and the food environment (e.g., high prices, limited variety). Participants proposed a range of strategies to promote fruit and intake, primarily emphasizing nutrition education and social marketing, but also suggesting interventions to enhance convenience, reduce costs, and improve access.ConclusionFindings underscore the need for multilevel interventions that move beyond individual-focused strategies to address broader environmental and structural determinants of dietary behavior. Adopting a food systems-oriented approach to fruit and vegetable promotion may enhance the relevance and effectiveness of public health initiatives.